Heartbeat Drumbeat - Hernandez, Irene Beltran, 1945- (Arte Público Press, 2017)
A young woman finds the course of her life influenced by her Navajo and Mexican heritage and especially by an older Navajo woman and a young Indian lawyer. A young woman finds the course of her life influenced by her Navajo and Mexican heritage and especially by an older Navajo woman and a young Indian lawyer. A coming-of-age story set in the multicultural American Southwest, Heartbeat Drumbeat is rich in descriptions of Native-American and Mexican coming-of-age rituals.